Git essentials : create, merge, and distribute code with Git, the most powerful and flexible versioning system available - Santacroce, Ferdinando (Community experience distilled., 2015)
If you are a software developer with little or no experience of versioning systems, or are familiar with other centralized versioning systems, then this book is for you. If you have some experience working with command lines or using Linux admin or just using Unix and want to know more about Git, then this book is ideal for you.